Self-rectifying resistive memory in passive crossbar arrays - Kanghyeok Jeon (Nature Portfolio, 2021)
Memory-centric computing refers to computing designs where the memory, rather than the processor is central in the architecture. Here, the authors demonstrate a self-rectifying resistive memory cell that exhibits impressive endurance, and low power consumption, making it suitable for memory-centric applications.